Telerehabilitation Readiness, Knowledge, and Acceptance of Future Physiatrists in the Philippines: An Online Survey During the COVID-19 Pandemic - Carl Froilan D. Leochico; Carl Froilan D. Leochico; Marc Francis J. Perez; Jose Alvin P. Mojica; Sharon D. Ignacio; Sharon D. Ignacio (Frontiers in Rehabilitation Sciences, 2022)
BackgroundClinical, educational, and research interest in telerehabilitation has not been widely explored until the COVID-19 pandemic. Amid the enduring pandemic, telerehabilitation remains part of the daily service, academic, and research responsibilities of residents in various training institutions worldwide.ObjectiveTo determine the Rehabilitation Medicine residents' current levels of telerehabilitation readiness, knowledge, and acceptance, their pattern of beliefs about telerehabilitation, and the factors affecting their readiness.MethodsAll bona fide residents from all training institutions in the Philippines were invited to participate in an online survey evaluating the following constructs: technological readiness (using the Technological Readiness Index or TRI 2.0); telerehabilitation knowledge (using an original multiple-choice examination); and telerehabilitation acceptance (using the Unified Theory of Acceptance and Use of Technology questionnaire). A pre-test and pilot test were conducted. The TRI responses were classified according to technology adoption segments to determine the respondents' pattern of beliefs about telerehabilitation.ResultsSixty-two residents participated (86.1% response rate). They had good telerehabilitation readiness (3.3 ± 0.4 out of 5), fair telerehabilitation knowledge (2.1 ± 1.1 out of 5), and excellent telerehabilitation acceptance (4.5 ± 0.6 out of 5). The majority were classified either as telerehabilitation skeptics (38.7%), pioneers (19.4%), or explorers (19.4%). The factors that significantly influenced telerehabilitation readiness were optimism, innovativeness, discomfort, and insecurity (p < 0.05).ConclusionDespite having favorable levels of telerehabilitation readiness and acceptance, the Rehabilitation Medicine residents showed fair telerehabilitation knowledge. Our results suggest the need for formal education and training on virtual rehabilitation care during residency.